Arab animation : images of identity - Sayfo, Omar, 1982- (Edinburgh University Press, 2021)
"Omar Sayfo textually analyses around 40 animation productions in Algeria, Egypt, Iraq, Jordan, Kuwait, the Palestinian Territories, Qatar, Saudi Arabia, Syria, Tunisia and the United Arab Emirates, from the 1930s until recently, showing how cartoons have engaged in the making and remaking of religious and political identities."--